S1 guidelines for the diagnosis and treatment of ichthyoses: update - Oji, Vinzenz; Haußer-Siller, Ingrid (Journal der Deutschen Dermatologischen Gesellschaft, 2017)
Ichthyoses are a group of rare genetic skin disorders that pose numerous clinical challenges, in particular with respect to the correct diagnosis and appropriate management. The present update of the German ichthyosis guidelines addresses recent diagnostic advances that have resulted in the Sorèze consensus classification. In this context, we provide an updated diagnostic algorithm, taking into account clinical features as well as the molecular genetic basis of these disorders. Moreover, we highlight current therapeutic approaches such as psychosocial support, balneotherapy, mechanical scale removal, topical therapy, and systemic retinoid therapy. General aspects such as the indication for physical therapy, ergotherapy, or genetic counseling are also discussed. The present update was consented by an interdisciplinary consensus conference that included dermatologists, pediatricians, human geneticists, and natural scientists as well as representatives of the German patient support organization Selbsthilfe Ichthyose e. V.